Urban Residence and Genetic Predisposition Underlying Breast Cancer Distribution in Iraq - Raheem Abd Zaid Al Abedi (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Breast cancer represents a major global health challenge and is the leading cause of oncological mortality among women. Specific Background In the Eastern Mediterranean region and specifically within Al-Najaf province, Iraq, registered cancer cases have risen significantly from 2020 to 2025, with breast malignancies consistently topping annual health registries across regional oncology facilities. Knowledge Gap Although structural risk factors are generally recognized, multi-center epidemiological data evaluating the overlapping influence of environmental, genetic, demographic, and lifestyle variables within this specific geographic population remain highly limited. Aims This investigation aimed to describe the temporal distribution of breast cancer cases in Al-Najaf province from 2020 to 2025 and identify associations with potential demographic, genetic, and environmental risk factors among 800 consecutively enrolled female patients across four public and private oncology centers. Results Statistical analysis demonstrated that urban residents accounted for 73.3% of cases, revealing a highly significant predominance compared to rural districts (p 0.05). A positive family history of breast or ovarian cancer was reported by 46.7% of patients, the peak age group was 40–60 years representing 56.7% of the cohort, and married women constituted 76.7% of cases. Locally advanced disease at stages II and III comprised 66.7% of diagnoses, with chemotherapy serving as the primary treatment modality. Novelty This study provides the first large-scale, multi-center evidence integrating private sector oncology data to demonstrate the critical role of urban living environments and hereditary patterns in southern Iraq. Implications These findings establish an urgent need for population-based screening programs, urban environmental mitigation strategies, and accessible genetic counseling infrastructure. Keywords: Breast Neoplasms, Risk Factors, Environmental Pollution, Genetics, Iraq Key Findings Highlights Urban residency demonstrates a statistically significant association with higher breast cancer frequency compared to rural environments. Hereditary predisposition is highly prevalent, with nearly half of the diagnosed cohort presenting a positive maternal family history. Locally advanced stages dominate clinical presentation, necessitating chemotherapy as the primary therapeutic management approach.